ORIENTATION OF COOPERATIVE MEMBERS RELATIONS - Hendrikus Pedro (Jurnal Scientia, 2022)
Cooperation is a alliance of people who make up the organization to achieve common goals. As a collection of people, the relationship between members and relationships between members and the group is a necessity. Variations in the background of the members allow for the diversity of motives, knowledge, experiences of cooperation and conflict of interest. Situations like this make relationships in a cooperation professionally managed to achieve common goals and become an important issue to be studied. This study aims to explain the dynamics of cooperation members' relationships with cooperation groups and their impact on the relationship between members and the existence of cooperation. Research with qualitative case study approach used in this research. One cooperation was involved in the study. The data collection process was conducted with FGD (Focused Group Discussion) on the members of the cooperation group and continued interviews on the two founding members and the cooperation movers. Data were analyzed using descriptive qualitative method. The results of data analysis show that member relationships with more exchange-oriented groups make members more focused on fulfilling rights and obligations and more communal-oriented relationships make members emphasize the warmth of relationships. Extreme exchange orientation eliminates the spirit of kinship and extreme communal orientation eliminates the professionalism of members' relationships with cooperation groups. An extreme orientation destroys relations between members and affects the destruction of the cooperation.